Biosynthesis of Zinc Oxide Nanoparticles via Leaf Extracts of Catharanthus roseus (L.) G. Don and Their Application in Improving Seed Germination Potential and Seedling Vigor of Eleusine coracana (L.) Gaertn - Dhruv Mishra; Manoj Kumar Chitara; Sweta Negi; Jagat Pal singh; Rajeew Kumar; Preeti Chaturvedi (Advances in Agriculture)
The ecofriendly nature of materials used in synthesis and their low cost make biosynthesized nanoparticles excellent stuff for a broad range of applications in bioscience. Green nanomaterials are progressively used in agriculture to deliver plant nutrients efficiently and effectively. The present work aimed to biosynthesize zinc oxide nanoparticles (ZnO NPs) utilizing Catharanthus roseus (L.) G. Don leaf extracts to use them as a nanopriming agent for improving seed germination and seedling growth in Eleusine coracana (L.) Gaertn (finger millet). UV-Vis spectroscopy, FTIR, FE-SEM, EDX, and TEM were used to characterize biosynthesized nanoparticles (NPs). The peaks at 362 nm characterized UV-Vis spectra of ZnO NPs. The FTIR absorption spectrum of ZnO NPs showed Zn-O bending at 547 cm−1. The size (44.5 nm) and shape (nonspherical) of ZnO NPs were revealed by TEM image analysis. XRD confirmed the hexagonal wurtzite phase of ZnO with an average particle size of 35.19. The seed germination results revealed that ZnO-nanoprimed seeds at 500 mg/L substantially improved all the seed germination parameters, viz., plumule length (23.4%), radicle length (55%), vigor index (41.94%), and dry matter production (54.6%) compared to hydropriming (control).